Gallium-containing mesoporous bioactive glass with potent hemostatic activity and antibacterial efficacy. Issue 1 (27th November 2015) - Pourshahrestani, Sara; Zeimaran, Ehsan; Adib Kadri, Nahrizul; Gargiulo, Nicola; Samuel, Shani; Naveen, Sangeetha Vasudevaraj; Kamarul, Tunku; Towler, Mark R.
Abstract : Gallium-containing mesoporous bioactive glass can be considered as an efficient hemostatic material due to its merits of increased platelet adhesion and thrombin formation as well as antibacterial properties. Abstract : Haemorrhage remains the leading cause of potentially survivable death in both military and civilian populations. Although a large variety of hemostatic agents have been developed, many of them have an inadequate capacity to induce hemostasis and are not effective in killing bacteria. In recent years, mesoporous bioactive glasses (MBGs) were found to be effective in inducing hemostasis. However, the materials may not be considered as ideal hemostats since they do not offer antimicrobial activity. The gallium ion (Ga +3 ) not only exhibits antibacterial properties but also accelerates the blood coagulation cascade. The aim of this study was to develop MBGs containing various concentrations of Ga2 O3 (1, 2 & 3 mol%) via the evaporation-induced self-assembly (EISA) process and investigate whether the addition of Ga 3+ would induce both hemostatic and antibacterial effects. The results indicated that the incorporation of lower Ga2 O3 content (1 mol%) into the MBG system improved structural properties including the specific surface area, mesopore size and pore volume as well as the release of silicon and calcium ions. The bioactive glass was found to stimulate blood coagulation, platelet adhesion and thrombus generation and exerted an antibacterial effect against both Escherichia coli and Staphylococcus aureus . Likewise, Ga-doped MBGs showed excellent cytocompatibility even after 3 days, with the 1% Ga2 O3 -containing MBG attaining the best biocompatibility that render them safe hemostatic agents for stopping bleeding. This study demonstrated that the lowest Ga2 O3 -substituted MBG can be a potent candidate for controlling haemorrhage and wound infection.